Aspek parasitologi Sarcoptes scabiei var. hominis: Parasitological aspects of Sarcoptes scabiei var. hominis - Wahdini, Sri; Sungkar, Saleha (Perhimpunan Entomologi Indonesia, 2023)
Sarcoptes scabiei (Dee Geer) is the mite that causes scabies or mange. The mites live in the skin layers of humans and mammals. Nowadays, S. scabiei is classified according to their hospes and S. scabiei that lives in human is called Sarcoptes scabiei var. hominis. Controlling and eradicating human scabies, especially at the community level, requires understanding scabies as a pathogen and its interaction with humans. This paper discusses the biology of S. scabiei var. hominis and the interactions between mites and humans as hosts.